E-mentoring program organized by the Turkish Association for Child and Adolescent Psychiatry during the COVID-19 pandemic - Ercan, Eyup Sabri; Tufan, Ali Evren; Kutuk, Ozlem Meryem; Percinel Yazici, Ipek (Springer, 2021)
[Abstract Not Available]